Optical control of AMPA receptors using a photoswitchable quinoxaline-2,3-dione antagonist - Barber, David M. (Royal Society of Chemistry, 2017)

(untitled) (Chem Sci)
AMPA receptors respond to the neurotransmitter glutamate and play a critical role in excitatory neurotransmission. They have been implicated in several psychiatric disorders and have rich pharmacology. Antagonists of AMPA receptors have been explored as drugs and one has even reached the clinic. We now introduce a freely diffusible photoswitchable antagonist that is selective for AMPA receptors and endows them with light-sensitivity. Our photoswitch, ShuBQX-3, is active in its dark-adapted trans-isoform but is significantly less active as its cis-isoform. ShuBQX-3 exhibits a remarkable red-shifting of its photoswitching properties through interactions with the AMPA receptor ligand binding site. Since it can be used to control action potential firing with light, it could emerge as a powerful tool for studying synaptic transmission with high spatial and temporal precision.